2004
DOI: 10.1021/ja047018k
|View full text |Cite
|
Sign up to set email alerts
|

A Design of Fluorescent Probes for Superoxide Based on a Nonredox Mechanism

Abstract: Fluorometric detection of O2-* is performed based on desulfonylation of 3 to the corresponding fluoresceins 4 through nucleophilic substitution, and this fluorescing process is quite specific toward O2-* over H2O2, t-BuOOH, NaOCl, 1O2, HO*, NO*, and ONOO-. Furthermore, effects of glutathione, cytochrome P450 reductase/NADPH, and diaphorase/NADH are relatively small on the fluorescing process of probe 3 with X = Y = F, which is useful to detect O2-* released from neutrophils stimulated by phorbol myristate acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
130
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 189 publications
(134 citation statements)
references
References 9 publications
3
130
0
1
Order By: Relevance
“…Other commonly used fluorescent dyes are based on rhodamine, ethidine and the phenoxazine backbones, well known examples include Amplex Red and Amplex Ultra Red which are based on phenoxazine (resourfin). Commonly used chemiluminescent based indicators include lucigenin as a specific detector for O 2¯• while luminol has mostly been used as an indicator for general ROS production.Based on redox active substituents in the benzene ring and using the nucleophilic character of some reactive species, the development of a new generation of dyes with potentially improved characteristics has been described [31][32][33][34][35][36][37][38][39][40].Because of the quite complex chemistry of all of these dyes, great care has to be taken in designing biological experiments and in their interpretation. For example, there is evidence that DCF may produce secondary radicals induced by its own oxidation [41].…”
Section: Dyesmentioning
confidence: 99%
“…Other commonly used fluorescent dyes are based on rhodamine, ethidine and the phenoxazine backbones, well known examples include Amplex Red and Amplex Ultra Red which are based on phenoxazine (resourfin). Commonly used chemiluminescent based indicators include lucigenin as a specific detector for O 2¯• while luminol has mostly been used as an indicator for general ROS production.Based on redox active substituents in the benzene ring and using the nucleophilic character of some reactive species, the development of a new generation of dyes with potentially improved characteristics has been described [31][32][33][34][35][36][37][38][39][40].Because of the quite complex chemistry of all of these dyes, great care has to be taken in designing biological experiments and in their interpretation. For example, there is evidence that DCF may produce secondary radicals induced by its own oxidation [41].…”
Section: Dyesmentioning
confidence: 99%
“…We have made initial progress in the development of small-molecule ratiometric probes [37] and reversible redox sensors [38]. Finally, although this review has focused specifically on NO and H 2 O 2 indicators, new fluorogenic reagents for peroxynitrite [39], hypochlorous acid [40], superoxide [41], highly reactive oxygen species [42], and global nitrative stress [43] have also been reported recently. The continuing interplay between chemical design and biological inquiry presages a rich future for studying the oxidation biology of the cell and its contributions to human health and disease.…”
Section: Small Molecule Fluorescent Probes For Hydrogen Peroxidementioning
confidence: 99%
“…Furthermore, CL is an effective method in research on ROS, because of the associated instantaneous nature of CL and the short lifetime of ROS radicals (11)(12)(13)(14)(15)(16). Goto et al (17) successfully investigated the CL mechanism of the alkalineearth metal peroxides (MgO 2 , BaO 2 ) with CL reagents (luminol and lucigenin), and demonstrated that the hydroxyl ( • OH) and • O 2 − were released chiefly on the MgO 2 and BaO 2 , respectively, with CL.…”
Section: Ros As Hydrogen Peroxide (H 2 O 2 ) Superoxide Anion ( • Omentioning
confidence: 99%